THE ANALYSIS OF PRICE, PROMOTION, AND PLACE AND THEN TO EFFECT ON CONSUMER DECISION MAKING A Study of Structural Equation Modeling in Healthcare Products - Ismulyana Djan; Fitriyanti . (The Management Journal of Binaniaga, 2017)
The purpose of this study is to determine the customer’s purchasing decision toward the product that directly influenced by the price variable, promotion variable and place variable, included analyzing the policy of price decision, promotion implementation and how important the place to decide customer’s purchasing decision. The method used in his study is survey method using Structural equation modeling (SEM) analyzing technique through AMOS application. The result of the study shows that the price influenced the purchasing decision making as (CR) 2,399 > 1,96, and the promotion influenced the purchasing decision making as (CR) 3,493 > 1,96, and the place did not influence the purchasing decision making as (CR) 1,089 < 1,96.Keyword : Structural Equation Modeling (SEM)